Design Lung Function Tests Device Using a Microcontroller - Kazem, Mahdi Kazem Gharkan; Sabr, Hussein Dhafer; Jodi, Hussein Jameel; Hussein, Murtadha Majid; Laftah, Hawraa Abbas (American Journal of Botany and Bioengineering, 2025)
The Lung Exerciser – 3 Ball Spirometer is a widely used device for improving lung function and preventing respiratory complications. In this project, we aim to enhance the functionality of the device by incorporating an IR sensor and LCD display, controlled by an Arduino microcontroller. The IR sensor is used to detect the movement of the three balls in the chamber, which is then converted into a time measurement to determine the length of the user’s breath. This information is displayed on an LCD screen, providing the user with feedback on their breathing pattern and progress. The Arduino microcontroller is programmed to collect and process the data from the IR sensor and display it on the LCD screen in a user-friendly format. The device can be calibrated based on the user’s individual lung capacity, ensuring accurate measurements and personalized feedback. The enhanced functionality of the Lung Exerciser – 3 Ball Spirometer device can provide several benefits, including increased motivation and engagement for users, improved accuracy and reliability of measurements, and the ability to track progress over time. Overall, this project demonstrates the potential for incorporating technology, such as the Arduino microcontroller, into medical devices to enhance their functionality and improve patient outcomes. The Lung Exerciser – 3 Ball Spirometer with IR sensor and LCD display provides a low-cost and non-invasive method for individuals with respiratory conditions to improve their lung function and breathing patterns.